1996
DOI: 10.1523/jneurosci.16-21-06676.1996
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Action-Potential Initiation and Na+Channel Densities in the Soma and Axon Initial Segment of Subicular Pyramidal Neurons

Abstract: A long-standing hypothesis is that action potentials initiate first in the axon hillock/initial segment (AH-IS) region because of a locally high density of Na+ channels. We tested this idea in subicular pyramidal neurons by using patch-clamp recordings in hippocampal slices. Simultaneous recordings from the soma and IS confirmed that orthodromic action potentials initiated in the axon and then invaded the soma. However, blocking Na+ channels in the AH-IS with locally applied tetrodotoxin (TTX) did not raise th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
229
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(242 citation statements)
references
References 38 publications
12
229
0
1
Order By: Relevance
“…These results provide evidence that the axonal recording sites were distal to the spike initiation zone, which has been estimated to be 30 -60 m from the soma in unmyelinated axons (Colbert and Johnston, 1996) but may be farther out in myelinated axons (Colbert and Pan, 2002). We reasoned that if our axonal recording sites had been upstream from the spike initiation zone, every somatic spike would have corresponded to an axonal success as the action potential back-propagated toward the soma.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…These results provide evidence that the axonal recording sites were distal to the spike initiation zone, which has been estimated to be 30 -60 m from the soma in unmyelinated axons (Colbert and Johnston, 1996) but may be farther out in myelinated axons (Colbert and Pan, 2002). We reasoned that if our axonal recording sites had been upstream from the spike initiation zone, every somatic spike would have corresponded to an axonal success as the action potential back-propagated toward the soma.…”
Section: Resultsmentioning
confidence: 77%
“…Because propagation failures were evident, however, the axonal recording electrode was more likely to have been beyond the spike initiation zone. As an additional test, we examined the axonal noise measurements for instances of spike-like events occurring in the absence of somatic action potentials, because axonal successes with somatic failures have been documented for axonal recordings between the soma and the spike initiation zone (Colbert and Johnston, 1996;Williams and Stuart, 1999). In our recordings, however, no axonal spikes were ever observed in the absence of a somatic action potential.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a complicated experimental issue for which direct evidence has been elusive. In what is arguably the most direct approach, voltage clamp of outside-out (11,12) and conventional cell-attached (13) membrane patches has been used to assess Na current density along the AIS. However, the fidelity of these approaches may be limited by localized geometric factors, such as Na channel anchoring by cytoskeletal elements (14) that may limit channel density in recorded membrane patches.…”
mentioning
confidence: 99%
“…Conflicting results have been reported. For example, a hyperpolarizing shift in voltage-dependence of Na channel activation in the distal AIS has been reported that would contribute to the AP initiation in distal AIS (11,12,17), but this difference in gating has not always been consistently observed (13).…”
mentioning
confidence: 99%